Thrombospondin‐1 mimic peptide PKHB1 induced endoplasmic reticulum stress‐mediated but CD47‐independent apoptosis in non‐small cell lung cancer. Issue 2 (4th January 2023) - Ye, Jiani; Yao, Yinan; Zhao, Jianfeng; Cui, Luyun; Lu, Guohua; Wang, Qing; Zhang, Pei; Zhou, Jianying
Abstract: Non‐small cell lung cancer (NSCLC) is one of the most common malignancies with high morbidity and mortality. PKHB1, a serum‐stable Thrombospondin‐1 (TSP‐1) mimic peptide, has shown some effective ability in triggering cell death against several cancers. Here, we aimed to study the potential biological function of PKHB1 and its molecular mechanism in NSCLC. Our results revealed that PKHB1 significantly suppressed NSCLC cell proliferation, cell migration, and induced apoptosis in a dose‐dependent manner. Additionally, we found that PKHB1 treatment resulted in mitochondrial transmembrane potential depolarization, Ca 2+ overloading as well as the upregulation of proapoptotic proteins. Mechanistically, PKHB1 induced NSCLC cells apoptosis in a CD47‐independent manner. Further study revealed that PKHB1 provoked endoplasmic reticulum (ER) stress principally through the activation of CHOP and JNK signaling, which could be alleviated in the presence of 4‐PBA, an ER stress inhibitor. Furthermore, xenograft tumor models showed that PKHB1 treatment could notably inhibit NSCLC tumor growth in vivo. In conclusion, these findings suggested that PKHB1 exerted antitumor efficacy in NSCLC via triggering ER stress‐mediated but CD47‐independent apoptosis, potentially functioned as a promising peptide‐based therapeutic agent for NSCLC.